Solvated Graphenes: An Emerging Class of Functional Soft Materials. (26th November 2012) - Cheng, Chi; Li, Dan
Abstract From a materials science point of view, graphene is essentially a polymer having a giant, two‐dimensional molecular configuration. In this Progress Report, solvated graphene and its derivatives are illustrated from the perspective of soft matter. Firstly, the key appealing features of graphene as a molecular building block for assembling bulk soft materials are highlighed. It is then demonstrated how the intersheet interactions in solution are correlated with the molecular structure of graphene, and how a combination of the unique molecular structure and colloidal interactions can lead to simple, solution‐phase approaches for assembling graphenes into a variety of macroscopic nanoarchitectures. A number of new exciting functions and applications are also highlighted, which are enabled by the solvation effect and in particular, it is discussed why and how solvated graphenes can offer exciting functions that are unattainable with the dried, hard counterpart. The discussion is concluded with some personal perspectives on the future directions in which this emerging class of functional soft materials could be pursued.